Energy deficiency selects crowded live epithelial cells for extrusion - Saranne J. Mitchell; Carlos Pardo-Pastor; Anastassia Tchoumakova; Thomas A. Zangle; Jody Rosenblatt (Nature, 2025)
Abstract Epithelial cells work collectively to provide a protective barrier, yet they turn over rapidly through cell division and death. If the numbers of dividing and dying cells do not match, the barrier can vanish, or tumours can form. Mechanical forces through the stretch-activated ion channel Piezo1 link both of the processes; stretch promotes cell division, whereas crowding triggers live cells to extrude and then die 1,2 . However, it was not clear what selects a given crowded cell for extrusion. Here we show that the crowded cells with the least energy and membrane potential are selected for extrusion. Crowding triggers sodium (Na + ) entry through the epithelial Na + channel (ENaC), which depolarizes cells. While those with sufficient energy repolarize, those with limited ATP remain depolarized, which, in turn, triggers water egress through the voltage-gated potassium (K + ) channels K v 1.1 and K v 1.2 and the chloride (Cl − ) channel SWELL1. Transient water loss causes cell shrinkage, amplifying crowding to activate crowding-induced live cell extrusion. Thus, our findings suggest that ENaC acts as a tension sensor that probes for cells with the least energy to extrude and die, possibly damping inadvertent crowding activation of Piezo1 in background cells. We reveal crowding-sensing mechanisms upstream of Piezo1 that highlight water regulation and ion channels as key regulators of epithelial cell turnover.